KRolog: A Prolog based interface for the Khepera robots - Ferretti, Edgardo (2006)
In this paper we present KRolog a Prolog based interface to work with simulated and real Khepera robots. The interface hides low-level robot-computer communication and provides a high-order set of predicates to develop programs in a declarative manner. This paper describes the software we have developed to support the hardware platform we use in cognitive robotics research at the LIDIC.